Maternal Deaths caused by COVID-19 Infection in the First Year of the Pandemic Wave - Akbar, Muhammad Ilham Aldika; Mulawardhana, Pungky; Wardhana, Manggala Pasca; Gumilar, Khanisyah Erza; Raheestyningtyas, Ecccita; Laksana, Muhammad Ardian Cahya; Anas, Jimmy Yanuar; , Ernawati; Joewono, Hermanto Tri; Bachnas, Muhammad Adrianes; Tjokroprawiro, Brahmana Askandar (Folia Medica Indonesiana, 2023)
Highlights: • These cases of maternal deaths caused by COVID-19 infections illustrated the significant risk factors for maternal mortality during the early phases of the pandemic, while studies had not extensively reported this. • COVID-19 infections increase the risk of maternal and neonatal mortality, with infants having a lower chance of survival even if they are delivered. • Respiratory support, antiviral medications, antibiotics, anticoagulants, and supportive care are the primary treatments for severe COVID-19 in pregnancy. Abstract This article presents seven cases of maternal deaths attributed to COVID-19 during the first year of the pandemic wave. These cases provide insights into the natural progression of COVID-19 in pregnant women who were not vaccinated. This study showed that COVID-19 significantly increased maternal and neonatal mortality and morbidity. All of the patients exhibited symptoms of fever, cough, and dyspnea upon admission to the hospital. They were admitted with elevated respiratory rates (26–32 times/minute) and low oxygen saturation (<95%). Four patients had obesity, while one patient had pregestational diabetes. The COVID-19 diagnosis was established using a rapid antibody or antigen test and chest X-ray, which indicated pneumonia. Medical interventions administered to the patients included antiviral therapy (5 patients), antibiotics (6 patients), and anticoagulants (4 patients). From a total of five babies delivered, four babies were delivered via cesarean section. Two babies were not delivered due to previability and maternal deaths before delivery. The patients passed away within 3–10 days of hospital admission. In conclusion, adequate and early intervention and management of pregnant women infected with COVID-19 are crucial in preventing maternal and neonatal deaths, especially in unvaccinated women.